Penerapan Model Rotating Trio Exchange Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran IPS - Zain, Rohainiah; Mahaendra, Yusril; Apriliana, Baiq; Khairiah, Izatul; Ilhami, M. Rofiqi (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2025)
This study was motivated by the low level of students’ understanding in Social Studies (IPS) at MTs Mu’allimin NWDI Pancor, as indicated by learning outcomes that had not yet reached the Minimum Mastery Criteria (KKM) and the lack of student engagement during learning activities. The dominance of the lecture method makes students passive, less trained in critical thinking, and unable to develop conceptual understanding independently or in groups. To address these issues, this study implemented the Rotating Trio Exchange learning model, a cooperative learning strategy that emphasizes structured discussions and information exchange in small groups. The purpose of this research was to improve students’ understanding of Social Studies through the application of the Rotating Trio Exchange model in the first semester of the 2025/2026 academic year. This research used a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 35 eighth-grade students. Data were collected using learning outcome tests, observation sheets for teacher and student activities, and documentation. The results showed that the Rotating Trio Exchange model improved students’ understanding, as seen from the increase in average scores from the pre-cycle to cycle I, and more significantly in cycle II. Student learning activities also increased through active discussions, idea-sharing, and responsibility in completing tasks. Thus, the Rotating Trio Exchange model is effective in improving students’ understanding in Social Studies and can serve as an innovative alternative learning model in schools